谐波传动中柔轮轮齿对柔轮变形的影响分析 - 储著金; 谭晶 (Jixie chuandong)
In traditional research of harmonic gear drive,the method used for solving the harmonic gear transmission conjugate tooth profile is generally based on the theory of envelope to solve conjugate tooth profile.The influence of the flexspline tooth isn’t considered in the process of formula derivation with the method,so the result gained is not accurate.Using UG software,the 3Dmodels of the elliptical cam wave generator,the cup-shaped flexspline and the simplify ring are built,the models are imported to the ANSYS finite element software by Parasolid format and analyzed.Using surface-surface contact element to solve the contacting problem between the flexspline and the wave generator is simulated.The displacement curve and elastic strain curve of the nodes located on neutral layer of the gear ring and the simplify ring is obtained.The influence of flexspline tooth on flexspline deformation is analyzed.A great reference value for solving harmonic gear tooth is provided.